1987
DOI: 10.1177/096032718700600116
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Plasma and Urine Paraquat Concentration

Abstract: 1 A non-exponential mathematical equation was used to extrapolate the 'predictive line' for plasma paraquat concentrations beyond 24 h. Plasma paraquat concentrations were measured in 30 patients who were admitted more than 24 h after overdose. The extrapolated line accurately predicted the outcome in 27 of these 30 patients. 2 Urine paraquat concentrations were measured in 53 patients. All patients with urine paraquat concentrations of less than 1 mg/l (colourless or light blue test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 3 publications
4
94
1
1
Order By: Relevance
“…Early prognosis of PQ poisoning is significant for both patients and doctors [3]. Studies have shown that the mortality rate of PQ poisoning is highly correlated with ingested PQ amount or PQ concentrations in plasma and urine (within 4-24 hr elapsed from ingestion) [4,5]. Hsu et al [6] found that early haemoperfusion (HP) after PQ exposure may reduce the mortality specifically and that HP <4.0 or <5.0 hr can reduce the relative risk of mortality by approximately 81% or 51%, respectively.…”
Section: Paraquat (11mentioning
confidence: 99%
“…Early prognosis of PQ poisoning is significant for both patients and doctors [3]. Studies have shown that the mortality rate of PQ poisoning is highly correlated with ingested PQ amount or PQ concentrations in plasma and urine (within 4-24 hr elapsed from ingestion) [4,5]. Hsu et al [6] found that early haemoperfusion (HP) after PQ exposure may reduce the mortality specifically and that HP <4.0 or <5.0 hr can reduce the relative risk of mortality by approximately 81% or 51%, respectively.…”
Section: Paraquat (11mentioning
confidence: 99%
“…7 PQ-poisoned patients whose urine PQ concentrations 24 h after ingestion ranged from 25 to 50 ppm (as well as those with poisoning over 50 ppm) experienced an 88.9% mortality rate due to the lack of a proper antidote. 8 At present, physicians treat PQ-poisoned patients on the spot with a standard PQ detoxification protocol in accordance with the detection results from a urine sodium dithionite assay and PQ poisoning symptoms. [9][10][11] However, a urine sodium dithionite assay cannot accurately reflect PQ poisoning prognosis in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Our paraquat-poisoned patient presented most of the validated indicators of poor outcome, including suicidal ingestion, ingestion of a large quantity (one mouthful of a 20% solution is potentially life-threatening), the presence of gastritis at gastroscopic examination, an early renal dysfunction, and elevated plasma paraquat concentration related to time of ingestion [1,8]. According to the survival probability employing Proudfoot's criteria [9] or Scherrmann's predictive value of plasma paraquat concentration [10], this patient was initially classified as likely to die. According to the Hart nomogram [11], his predicted survival rate was of 20-30%.…”
Section: Discussionmentioning
confidence: 99%